Hero Archetypes Analysis of Super Mario Bros (2023) Movie - Muhammad Daffa; Dina Amelia (English Teaching Journal : A Journal of English Literature, Language and Education, 2024)
This study aims to provide theoretical and practical insights into literary work analysis. Theoretically, the research is supposed to advance knowledge of literary criticism, particularly Jung's archetypal ideas. Practically, the research is predicted to be valuable for future studies in using archetypes in literary criticism for individuals eager to investigate and deepen their understanding of hero archetypes. This study adopts a descriptive and qualitative research analysis method. There were found five archetypes from twelve hero archetypes. There are, The Innocent, Ruler, Destroyer, Warrior, and Lover. This study not only focuses on the complexity of character development, but also the reoccurring narrative scenes. A thorough analysis of important scenes, dialogues, and moments throughout the film reveals how each character portrays different characteristics of the hero archetype.